The shaming of people with disabilities in clinical practice: a bioethical critique - Andrade, Gabriel; Redondo, Maria Campo (Medicina e Morale, 2022)
Shaming is defended by some as a necessary measure of social control. But shaming is unjust to the extent that it is disproportionate, and largely counterproductive. While much progress has been made, people with disabilities are still frequently at the receiving end of shaming. This is manifest in disregard for accommodation requests, condescending attitudes and overall lack of empathy towards people with disabilities. These trends are also manifest in clinical settings. Medical staff and healthcare workers need to seriously consider this state of affairs and embrace attitudinal changes and policies that contribute to a more welcoming atmosphere towards the disabled, and consequently curb the shaming to which they have been traditionally exposed.